Analysis of the state of knowledge and awareness in the area of tick-borne diseases prophylaxis in the population at occupational risk - Cisak, Ewa; Zwoliński, Jacek; Chmielewska-Badora, Jolanta; Dutkiewicz, Jacek; Wójcik-Fatla, Angelina; Zając, Violetta (Polish Journal of Public Health, 2011)
Introduction. Diseases transmitted by ticks, also called transmissive diseases, belong to zoonoses and constitute a serious problem, especially in forestry and agricultural envinronment, as occupational diseases. Aim. The objective of the study was an evaluation of the state of knowledge of tick-borne diseases and prevention measures in forestry workers. Material and methods. An anonymous survey was conducted among 157 forest exploitation workers employed in 4 forest inspectorates subordinated to the Regional Management of National Forests in Lublin. The questionnaire form consisted of questions concerning clinics, epidemiology and prophylaxis of tick-borne diseases, using personal protection at work and suggestions and expectations of forestry workers concerning the prophylaxis of borreliosis and other tick-borne diseases. Results. The majority out of 157 forestry workers (87.3%) revealed basic knowledge in the scope of tick-transmitted diseases. The most frequent preventive activities were: vaccinations against tick-borne encephalitis (80% of all examined), prophylactic medical examinations (over 90%) and application of repellents on the skin at work (75%). Among expectations, the most frequent replies concerned suggestions of more frequent prophylactic examinations (37% of respondents), as well as dissemination of educational materials. Conclusions. Forestry workers possess basic knowledge in epidemiology and prophylaxis of tick-borne diseases. Prophylaxis of tick-borne diseases among population groups at high occupational risk, including prophylactic examinations and educational activities, should be among the principal tasks of occupational medicine and OSH services.